Impact of a supervised twelve-week combined physical training program in heart failure patients: A randomized trial - Fabri, Tainá [UNESP]; Catai, Aparecida Maria; Ribeiro, Fábio H. O. [UNESP]; Junior, Jonas A. Araújo [UNESP]; Milan-Mattos, Juliana; Rossi, Danielle A. A. [UNESP]; Coneglian, Regina C. [UNESP]; Borra, Ricardo C.; Bazan, Silmeia Garcia Zanati [UNESP]; Hueb, João Carlos [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Roscani, Meliza Goi (Hindawi, 2019)
Purpose. The aim of this study was to compare the effects of supervised combined physical training and unsupervised physician-prescribed regular exercise on the functional capacity and quality of life of heart failure patients. Methods. This is a longitudinal prospective study composed of 28 consecutive heart failure with reduced ejection fraction patients randomly divided into two age- and gender-matched groups: trained group (n = 17) and nontrained group (n = 11). All patients were submitted to clinical evaluation, transthoracic echocardiography, the Cooper walk test, and a Quality of Life questionnaire before and after a 12-week study protocol. Categorical variables were expressed as proportions and compared with the chi-square test. Two-way ANOVA was performed to compare the continuous variables considering the cofactor groups and time of intervention, and Pearson correlation tests were conducted for the associations in the same group. Results. No significant differences between groups were found at baseline. At the end of the protocol, there were improvements in the functional capacity and ejection fraction of the trained group in relation to the nontrained group (p<0.05). There was time and group interaction for improvement in the quality of life in the trained group. Conclusions. In patients with heart failure with reduced ejection fraction, supervised combined physical training improved exercise tolerance and quality of life compared with the unsupervised regular exercise prescribed in routine medical consultations. Left ventricular systolic function was improved with supervised physical training.